VR-Banway: deploying a body area network gateway on single-board computers and mesh networks - Abade, Pedro António Carvalho (2017)
Internet of Things (IoT) is a generic category of ICT architectures that includes the use of sensor-based, communication-enabled systems. A common architectural element in IoT is the sensors gateway that collects data from nearby sensors and relays them to higher-order remote services. The VR2Market project, in which this work is integrated, uses two implementations of the gateway, based on Android smartphones and RPI boards. With the new proposed IoT-inspired computing module, it is possible to migrate gateways to a smaller, more efficient hardware, while retaining the high-level programming abstraction. In this work, we propose and implement a new version of the gateway, named VR-Banway, using the Intel Edison compute module, taking into consideration the integration with additional service layers in VR2Market system, especially with respect to the required Ad hoc networks support. VR-Banway proved to be a solution capable of replacing the existing gateway component in the VR2Market system. The new approach uses a smaller module, reduces power consumption and is more portable. VR-Banway has been used in the context of firefighters monitoring, but is ready to be deployed in other domains.